Smart collection & delivery routing problem - Yap, Aaron Jia Cheng (Nanyang Technological University, 2022)
Vehicle Routing Problem with Backhaul and Mixed load (VRPBM) extends the classical Vehicle Routing Problem (VRP), where a single vehicle can handle both delivery and collection. Both backhaul and linehaul addresses are treated the same in this solution version. Similar addresses are grouped and are considered as one unique location. A basic VRP route for these unique locations is generated using Google OR-Tools. The route is then checked to ensure the sequence fulfil all VRPBM requirements. A swapping method is used to swap locations if the current sequence fails. This version of VRPBM is compared against the classic VRP, and the improvement in number of vehicles, distance, duration and other matrices are reported.